Androgen Deprivation Therapy Toxicity and Management for Men Receiving Radiation Therapy. (30th December 2012) - Johnson, Matthew E.; Buyyounouski, Mark K.
Abstract : Androgen deprivation therapy is commonly used in combination with radiotherapy as part of the definitive treatment for men with clinically localized and locally advanced prostate cancer. Androgen deprivation has been associated with a wide range of iatrogenic effects impacting a variety of body systems including metabolic, musculoskeletal, cardiovascular, neurocognitive, and sexual. This review aims to provide the radiation oncology community with the knowledge to monitor and manage androgen deprivation therapy toxicity in an effort to provide the highest level of care for patients and to minimize the iatrogenic effects of androgen deprivation as much as possible.